Effect of genotype on changes in intelligence quotient after dietary relaxation in phenylketonuria and hyperphenylalaninaemia. Issue 3 (1st March 2000) - Greeves, Lindsey G; Patterson, Christopher C; Carson, Dennis J; Thom, Ruth; Wolfenden, Melanie C; Zschocke, Johannes; Graham, Colin A; Nevin, Norman C; Trimble, Elisabeth R
Abstract : BACKGROUND: Associations between genotype and intellectual outcome in patients with phenylketonuria are complicated because intelligence is influenced by many variables, including environmental factors and other genetic determinants. Intellectual changes with age, both on and after relaxation of diet, vary within the patient population. This study aims to determine whether a significant association exists between genotype and change in intelligence after relaxation of diet. METHODS: 125 patients with hyperphenylalaninaemia and phenylketonuria whose diet was relaxed after 8 years of age. Verbal, performance, and full scale intelligence quotients at 8, 14, and 18 years were expressed as standard deviation scores (IQ-SDS), and genotype as predicted residual enzyme activity (PRA) of phenylalanine hydroxylase. RESULTS: IQ-SDS at 8, 14, and 18 years were significantly below normal; no association was found between PRA and IQ-SDS. Significant reductions in verbal and full scale IQ-SDS occurred between 8 and 14 years and 8 and 18 years. There was a significant association between PRA and the reduction in verbal, performance, and full scale IQ between these years. Multiple regression analysis of 18 year results, using 8 year results as covariates, supported the association between PRA and IQ-SDS; after adjustment for phenylalanine control, both up to and after the age of 8 years, the full scale IQ-SDS at 14 and 18 years was 0.15 higher for each 10% increase in PRA. CONCLUSIONS: Genotype might be useful in predicting the likelihood of intellectual change in patients with hyperphenylalaninaemia and phenylketonuria whose diet is relaxed after the age of 8 years.